(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2020)
The study is basically capturing the effect of increasing non-performing assets on different dimensions of Indian banking sector. These dimensions include liquidity, solvency, profitability, capital adequacy & operating capability. The dimensions will be measured through different financial ratios. Financial reports of 06 banks composed of three public sector banks, namely Punjab national bank (PNB), State bank of India (SBI), and Union Bank of India (UBI) and three of private sector banks namely HDFC Bank, ICICI Bank & Axis Bank was used to analyze effect of NPA’s for ten years (2010-2019) on financial ratios comparing the net NPA to net advances, liquid asset to total asset ratio, total liabilities to total shareholder’s fund, return on assets, bank’s capital to risk weighted assets and operating expenses to total assets. Through correlation and regression analysis, a model was established, and it is found that only one variable ROA turns as a significant influencer among them. It means turning of performing assets into non-performing asset directly affecting the profitability of banking sectors.